Adaptasi digital, penguatan karakter dan inovasi kolaboratif di MI/SD - Hidayati, Arina Manasikana (Maliki Interdisciplinary Journal, 2026)
The development of the Industrial Revolution 4.0 has significantly transformed the educational landscape, particularly at the Madrasah Ibtidaiyah (MI) and elementary school levels. Digital transformation requires educators to adapt to technological advancements and integrate innovative teaching methods that align with contemporary needs. This study aims to examine the importance of digital adaptation, character strengthening, and collaborative innovation in improving the quality of primary education. The method employed is a literature review by analyzing various references related to education in the digital era. The findings reveal that teachers play a strategic role not only as knowledge transmitters but also as character builders and facilitators of technology-based learning. Strengthening digital literacy, pedagogical competence, and teacher character are essential to addressing globalization challenges. Furthermore, collaboration among schools, families, and communities is crucial in creating an adaptive and sustainable educational ecosystem. By optimizing the use of technology and reinforcing character values, MI/SD education is expected to produce competent, ethical, and future-ready generations capable of navigating global challenges.